SYSTEM OF PERSONNEL MANAGEMENT: WHEN HONOR IS MORE EXPENSIVE THAN MONEY - S. G. Kornienkov; D. V. Gritsaenko (Литьë и металлургия)
All forms of rewards of employees for successful fulfillment of importance tasks are considered in detail.